Ablative Fractional CO2 Laser for Facial Atrophic Acne Scars - Xu, Yaqin; Deng, Yunhua (Facial Plastic Surgery, 2018)
Ablative fractional carbon dioxide laser resurfacing is a well-established treatment for acne scars. However, there are limited consensus and guidelines regarding the procedure, such as its treatment plan, efficacy, and safety. In this study, we performed a systematic review to assess the efficacy and safety of the fractional carbon dioxide laser treatment procedure, and to provide evidence-based recommendations concerning its practical use on atrophic acne scars. A comprehensive search was performed in, EMBASE, Ovid, Web of Science, and Cochrane databases, using the keywords “scar(s),” “acne vulgaris,” “carbon dioxide,” and “fraction* laser(s)” for the period from January 1987 to December 2016. The initial literature search identified 337 articles. The final selection included 30 studies: 12 retrospective studies and 18 prospective randomized clinical trials. Ablative fractional carbon dioxide laser is an effective therapy for the treatment of acne scars. The treatment session, interval, and parameters should be customized for each patient. Combination therapy should be considered for ice-pick type acne scars. The use of dermocosmetics in pre- and postoperative care may be beneficial to patients.
Keywords: acne scars; carbon dioxide laser; fractional lasers